Material manipulável estruturado versus Applet no desenvolvimento do pensamento algébrico ao nível do 1º Ciclo do Ensino Básico - Santos, Nuno (2017)
This investigation was conducted in the framework of the master's degree in Preschool Education and teaching of the first cycle of basic education, with students of a class of third-year elementary schooling in a Castelo Branco elementary school. Through this study, we intend to examine whether digital technology improving the number of success cases and decisionmaking in solving mathematical tasks involving repetition patterns, compared the tasks solved by using the standard blocks. This research, comparative in nature, was based on a mixed approach (quantitative and qualitative) data processing level. Our intervention was structured in 3 phases. In the first phase, the 23 students who made up the class solved 4 tasks with repeating patterns through a work record (repeating Patterns: ABAB, ABCABC, ABBABB e ABBCCABBCC). The responses of students, in the schedule of work, were analyzed through a holistic scale focused adaptation of [1], in which it was ranked each response between 0 to 2 points. From the ratings obtained by students, the class was divided into 2 homogenous groups. On the other hand, in the second phase, the students who were part of the Group (11 students) solved the same tasks using an applet, while students who comprised the Group B (12 students) solved the same tasks through manipulable material (standard blocks). To proceed to correction of the tasks of the group, we ran the ' screenshots ' to computer screens for each task. On the other hand, the answers of the students of Group B were analyzed using not only to work but also the photos of the compositions performed. In the third stage we proposed the same tasks, in which all students in the class, decided the issues through a worksheet. After the data analysis we found that there were no statistically significant differences between the results obtained by the students who worked with the applet compared students who worked with manipulable materials. Although both groups of the 1st to the 3rd stage have improved substantially in terms of decision-making, as well as the number of replies considered assertive, but not so complete that work with the applet was better for the work with manipulable materials.